Apolipoprotein E Enhances microRNA-146a in Monocytes and Macrophages to Suppress Nuclear Factor-κB–Driven Inflammation and Atherosclerosis - Li, Kang (Circ Res, 2015)
RATIONALE: Apolipoprotein E (apoE) exerts anti-inflammatory properties that protect against atherosclerosis and other inflammatory diseases. However, mechanisms by which apoE suppresses the cellular activation of leukocytes commonly associated with atherosclerosis remain incompletely understood. OBJECTIVE: To test the hypothesis that apoE suppresses inflammation and atherosclerosis by regulating cellular microRNA levels in these leukocytes. METHODS AND RESULTS: An assessment of apoE expression among such leukocyte subsets in wild-type mice revealed that only macrophages and monocytes express apoE abundantly. An absence of apoE expression in macrophages and monocytes resulted in enhanced nuclear factor-κB (NF-κB) signaling and an exaggerated inflammatory response upon stimulation with lipopolysaccharide. This correlated with reduced levels of microRNA-146a, a critical negative regulator of NF-κB signaling. Ectopic apoE expression in Apoe(−/−) macrophages and monocytes raised miR-146a levels, while its silencing in wild-type cells had an opposite effect. Mechanistically, apoE increased the expression of transcription factor PU.1, which raised levels of pri-miR-146 transcripts, demonstrating that apoE exerts transcriptional control over miR-146a. In vivo, even a small amount of apoE expression in macrophages and monocytes of hypomorphic apoE mice led to increased miR-146a levels, and inhibited macrophage pro-inflammatory responses, Ly-6C(high) monocytosis, and atherosclerosis in the settings of hyperlipidemia. Accordingly, cellular enrichment of miR-146a through the systemic delivery of miR-146a mimetics in Apoe(−/−)Ldlr(−/−) and Ldlr(−/−) mice attenuated monocyte/macrophage activation and atherosclerosis in the absence of plasma lipid reduction. CONCLUSIONS: Our data demonstrate that cellular apoE expression suppresses NF-κB–mediated inflammation and atherosclerosis by enhancing miR-146a levels in monocytes and macrophages.